2017
DOI: 10.1177/1043659616686167
|View full text |Cite
|
Sign up to set email alerts
|

Refugee and Immigrant Women’s Experience of Postpartum Depression: A Meta-Synthesis

Abstract: The aim of this work is to synthesize qualitative research on refugee and immigrant women's experiences of postpartum depression (PPD) to gain insight into the unique needs of this group of women. This population is more at risk of developing PPD due to a complexity of issues including pre- and postmigratory stressors; however, there is currently little research on this topic available to health care providers and policy makers. Thirteen articles met inclusion criteria, and five themes emerged from the meta-sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 29 publications
2
49
0
1
Order By: Relevance
“…"I think that [PND] As this review identifies (along with Dennis and Chung-Lee, 2006;Hadfield and Wittkowski, 2017;Tobin et al, 2018), the attitudes of HCPs and their relationship with women influence a woman's choice to seek help. With HCPs facing pressures from a number of sources in practice, such as time constraints and lack of continuity, it is possible that professionals are struggling to build a relationship with the women they see.…”
Section: Familymentioning
confidence: 99%
See 2 more Smart Citations
“…"I think that [PND] As this review identifies (along with Dennis and Chung-Lee, 2006;Hadfield and Wittkowski, 2017;Tobin et al, 2018), the attitudes of HCPs and their relationship with women influence a woman's choice to seek help. With HCPs facing pressures from a number of sources in practice, such as time constraints and lack of continuity, it is possible that professionals are struggling to build a relationship with the women they see.…”
Section: Familymentioning
confidence: 99%
“…They reported complex and interrelated themes relating to the process of help, relationships with HCPs and the importance of continuity of care as well as education for HCPs regarding PND. Tobin et al's (2018) review investigated refugee and immigrant women's experiences of PND with barriers and facilitators to help-seeking being two of the identified themes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an integrative review of the literature examining the potential influence of HCPs' attitudes and behaviours on health-care disparities 80 used a 'broad definition' and included all groups that, owing to ethnicity, place of birth, citizenship, residence status or the related variables, have minority status in the country in which they reside. The same approach is taken by a meta-synthesis 81 undertaken on refugee and immigrant women's experience of postpartum depression in three major European countries with high levels of immigration (Germany, Italy and the UK). The authors of this aforementioned meta-synthesis noted that there is inconsistency in the use of the term immigrant and thus 'extended the inclusion criteria to all articles, where research had been undertaken on "ethnic minorities", "migrants", "refugees" and "asylum seekers" in the given country'.…”
Section: Urquia and Gagnon 76mentioning
confidence: 99%
“…The authors of this aforementioned meta-synthesis noted that there is inconsistency in the use of the term immigrant and thus 'extended the inclusion criteria to all articles, where research had been undertaken on "ethnic minorities", "migrants", "refugees" and "asylum seekers" in the given country'. 81 It is observed that 'nationality' is also used in maternity care-related research to classify immigrant women. For example, acknowledging the challenge of categorising immigrant and ethnic minority women, Jentsch et al 82 used 'overseas nationals' in their study.…”
Section: Urquia and Gagnon 76mentioning
confidence: 99%